3D Tele-Medical Speech Therapy using Time-of-Flight Technology - Stürmer, Michael; Maier, Andreas; Schaller, Christian; Soutschek, Stefan; Penne, Jochen; Handschu, Rene; Scibor, Mateusz; Nöth, Elmar (4th European Congress for Medical and Biomedical Engineering, 2009)
Tele-medical applications allow the treatment of patients over long distances. This is of special importance in speech therapy, since speech therapists often operate in specialized centers for certain disorders. In this paper we propose a novel therapy system which employs Time-of-Flight (ToF) 3D cameras that acquire 3D surface data in real time. The distance data is compressed within a MPEG stream and transmitted to a remote client where a 3D visualization is implemented. The loss in accuracy compared to the original data is within 1.6 mm and 9.7 mm. The system can be used for real-time streaming.
Keywords: Speech Therapy; Time-of-Flight; Telemedicine; MPEG

Alignment of multiple Time-of-Flight 3D Cameras for Reconstruction of walking feet - Stürmer, Michael; Seiler, Claude; Becker, Guido; Hornegger, Joachim (ISB2011 Brussels, Conference book Program & Abstracts, 2011)

Assessment of Time-of-Flight Cameras for Short Camera-Object Distances - Stürmer, Michael; Becker, Guido; Hornegger, Joachim (Vision, Modeling, and Visualization (2011), 2011)

Immersive Painting - Soutschek, Stefan; Hönig, Florian Thomas; Maier, Andreas; Steidl, Stefan; Stürmer, Michael; Erzigkeit, Helmut; Hornegger, Joachim; Kornhuber, Johannes (Proceedings of the ArtsIT 2009, 2009)

Inverse C-arm positioning for interventional procedures using real-time body part detection - Schaller, Christian; Rohkohl, Christopher; Penne, Jochen; Stürmer, Michael; Hornegger, Joachim (Springer-verlag, 2009)
The automation and speedup of interventional therapy and diagnostic workflows is a crucial issue. One way to improve these workflows is to accelerate the image acquisition procedures by fully automating the patient setup. This paper describes a system that performs this task without the use of markers or other prior assumptions. It returns metric coordinates of the 3-D body shape in real-time for inverse positioning. This is achieved by the application of an emerging technology, called Time-of-Flight (ToF) sensor. A ToF sensor is a cost-efficient, off-the-shelf camera which provides more than 40,000 3-D points in real-time. The first contribution of this paper is the incorporation of this novel imaging technology (ToF) in interventional imaging. The second contribution is the ability of a C-arm system to position itself with respect to the patient prior to the acquisition. We are using the 3-D surface information of the patient to partition the body into anatomical sections. This is achieved by a fast two-stage classification process. The system computes the ISO-center for each detected region. To verify our system we performed several tests on the ISO-center of the head. Firstly, the reproducibility of the head ISO-center computation was evaluated. We achieved an accuracy of (x: 1.73±1.11 mm/y: 1.87±1.31 mm/z: 2.91±2.62 mm). Secondly, a C-arm head scan of a body phantom was setup. Our system automatically aligned the ISO-center of the head with the C-arm ISO-center. Here we achieved an accuracy of ± 1 cm, which is within the accuracy of the patient table control. © 2009 Springer-Verlag.
UnivIS-Import:2015-04-16:Pub.2009.tech.IMMD.IMMD5.invers_6

Standardization of intensity-values acquired by Time-of-Flight-cameras - Stürmer, Michael; Penne, Jochen; Hornegger, Joachim (2008 IEEE Computer Society Conference on Computer Vision and Pattern Recognition Workshops, CVPR Workshops, 2008)
The intensity-images captured by Time-of-Flight (ToF)-cameras are biased in several ways. The values differ significantly, depending on the integration time set within the camera and on the distance of the scene. Whereas the integration lime leads to an almost linear scaling of the whole image, the attenuation due to the distance is nonlinear, resulting in higher intensities for objects closer to the camera. The background regions that are farther away contain comparably low values, leading to a bad contrast within the image. Another effect is that some kind of specularity may be observed due to uncommon reflecting conditions at some points within the scene. These three effects lead to intensity images which exhibit significantly different values depending on the integration time of the camera and the distance to the scene, thus making parameterization of processing steps like edge-detection, segmentation, registration and threshold computation a tedious task. Additionally, outliers with exceptionally high values lead to insufficient visualization results and problems in processing. In this work we propose scaling techniques which generate images whose intensities are independent of the integration time of the camera and the measured distance. Furthermore, a simple approach for reducing specularity effects is introduced. © 2008 IEEE.

Time-of-Flight 3-D Endoscopy - Penne, Jochen; Höller, Kurt Emmerich; Stürmer, Michael; Schrauder, Thomas; Schneider, Armin; Engelbrecht, Rainer; Feußner, Hubertus; Schmauß, Bernhard; Hornegger, Joachim (Springer-verlag, 2009)
This paper describes the first accomplishment of the Time-of-Flight (ToF) measurement principle via endoscope optics. The applicability of the approach is verified by in-vitro experiments. Off-the-shelf ToF camera sensors enable the per-pixel, on-chip, real-time, marker-less acquisition of distance information. The transfer of the emerging ToF measurement technique to endoscope optics is the basis for a new generation of ToF rigid or flexible 3-D endoscopes. No modification of the endoscope optic itself is necessary as only an enhancement of illumination unit and image sensors is necessary. The major contribution of this paper is threefold: First, the accomplishment of the ToF measurement principle via endoscope optics; second, the development and validation of a complete calibration and post-processing routine; third, accomplishment of extensive in-vitro experiments. Currently, a depth measurement precision of 0.89 mm at 20 fps with 3072 3-D points is achieved. © 2009 Springer-Verlag.
UnivIS-Import:2015-04-16:Pub.2009.tech.IMMD.IMMD5.timeof_24

Touchscreen ohne Touch - Berührungslose 3D Gesten-Interaktion für den Operationssaal (Touchscreen without Touch - Touchless 3D Gesture Interaction for the Operation Room) - Penne, Jochen; Soutschek, Stefan; Stürmer, Michael; Schaller, Christian; Placht, Simon; Kornhuber, Johannes; Hornegger, Joachim (i-com : Zeitschrift für interaktive und kooperative Medien, 2009)